Assessing the Effect of Irrigation Using Different Water Resources on Characteristics of Mild Cadmium-Contaminated Soil and Tomato Quality - Jiaxin Cui; Ping Li; Xuebin Qi; Wei Guo; Shafeeq Ur Rahman (Agronomy, 2022)
As the world economy and society have developed quickly, the amount of farmland soil pollution has become alarming, which has seriously threatened global food security. It is necessary to take effective measures on the moderately contaminated soil to produce high-quality food and to protect food security worldwide by effective use of land resources. Our experimental design was to study the changes in soil physicochemical properties and tomato yield and quality indicators by irrigating tomatoes on cadmium-contaminated soil with two different water qualities (reclaimed water irrigation: RW; tap water irrigation: TW) through drip irrigation devices. Tomato quality indicators were determined using plant physiological assays, as well as vitamin C (VC), total acidity (TA), protein content (PC), and soluble sugar content (SS). We tested five different types of cadmium-contaminated soils (less than 0.60 mg/kg, 0.60–1.20 mg/kg, 1.20–1.80 mg/kg, 1.80–2.40 mg/kg, 2.40–3.00 mg/kg) against RW and TW, and performed high-throughput sequencing of the soils to obtain environmental results for soil microbial diversity. The results reveal that compared with the TW condition, soil nutritional status was increased with the irrigated RW. The yield of the tomatoes increased by 52.03–94.03% than TW. The results of the study showed significant and highly significant relationships between tomato quality indicators (TA, SS, yield) and soil physical and chemical properties indicators (p < 0.01, 0.05). For instance, the RW increased the SOM by 6.54–12.13%, the TP by 0.48–24.73%, the yield of the tomatoes by 52.03–94.03% than TW, while the cadmium content did not show significant differences (p < 0.05), and the cadmium content did not increase the soil’s pollution level. Compared with TW treatment, RW treatment alleviated the inhibition of soil microbial diversity by cadmium and RW also increased its soil microbial diversity. The relative abundance of Proteobacteria, Gemmatimonadetes, and Bacteroidetes in the RW condition were higher than in the TW condition at different cadmium concentrations. In conclusion, RW improved the overall quality conditions of soil and the diversity of microbial communities, and did not aggravate the pollution degree of cadmium-contaminated soil, and affected the yield of tomatoes positively. RW can be an effective irrigation technique to reduce the use of clean water.